Circular economy supply chains : from chains to systems - Bals, Lydia; Tate, Wendy L.; Ellram, Lisa M. (Bingley, U.K. : Emerald Publishing Limited, 2022)
A circular economy perspective embraces a notion that we design everything to be reused for as long as possible, and then recaptured and repurposed when reuse is no longer possible. Designing for a circular economy ecosystem requires a more holistic, integrative viewpoint, spanning all aspects of design and development and considering many supply chain actors, far beyond that of traditional supply chains. Circular Economy Supply Chains highlights the need for cross-industry flows and the need for different actors (beyond producers and consumers) in circular value cycles. While biomimicry provides the structure for organizing the book, individual chapters build on other theoretical lenses and concepts, such as stakeholder theory. This book intends to move beyond a buyer-supplier view, embracing a holistic network or ecosystem view, to consider a cross-industry system perspective, where there is a diversity of actors needed for a working ecosystem. This edited book offers a comprehensive overview of system components and actors, including how the circular economy adds value, the role of producers and consumers, the spectrum of recovery possibilities to return products back to the consumption supply chain, and the essential role of information management.
1: Introduction to circular economy requirements: From supply chains to value systems -- Chapter 1. Introduction to circular economy supply chains: From supply chains to value systems / Lydia Bals, Wendy L. Tate and Lisa M. Ellram -- Chapter 2. Industrial symbiosis: Novel supply networks for the circular economy / Weslynne S. Ashton,Marian R. Chertow, and Shahana Althaf -- Chapter 3. No rest for the complex: Information flows, adaptation, and emergence in circular supply systems / Elizabeth Miller 2: The Role of Production (Actor: Producers) -- Chapter 4. Shaping the transition from linear to circular supply chains / Jennifer Rogan, Frank Fürstenberg, and Andreas Wieland -- Chapter 5. Circular business models: A network approach to promote circularity and value co-creation from the producer's perspective / Katharina Spraul and Stephanie Stumpf 3: The Role and Types of (Reverse) Logistics (Actors: Scavengers And Decomposers) -- Chapter 6. The effects of recycling locations on closed-loop supply chain performance / Petchprakai Sirilertsuwan -- Chapter 7. Stakeholder theory and supply chains in the circular economy / Muhammad Umair Shah,James H. Bookbinder 4: The Role and Types of Business and Retail Consumers (Actor: Consumers) -- Chapter 8. From end-of-the-road to critical node: The role of end-user "consumers" in shaping circular supply chain management / Ben Hazen, Ilenia Confente, Dan Pellathy, and Ivan Russo -- Chapter 9. Secondary markets: Enabling the circular economy / Dale S. Rogers, Haozhe Chen, and Zachary S. Rogers 5: The Role of Information and Financial Flows (Main Actor: Decomposers) -- Chapter 10. Blockchain technology and the circular economy: An exploration / Mahtab Kouhizadeh, Qingyun Zhu, Lojain Alkhuzaim, and Joseph Sarkis -- Chapter 11. Towards sustainability: A review of analytical models for circular supply chains / Ali Ülkü, Dawne M. Skinner, and Gonca Yildirim 6: The Role of the Business Context (Policy Makers, Ngos, Etc.) -- Chapter 12
Includes index.
Print version record.
Keywords: elektronické knihy; electronic books; Business logistics; Sustainable development; Business & Economics, Logistics & Supply Chain; Purchasing & supply management